Optimization Of Media Compositions And Fermentation Conditions For Enhancement of Surfactin Production By Response Surface Methodology (RSM) - Tengku Ab Rahman bin Tengku Nawawi
Surfactin is a lipopeptide biosurfactant produced by various strain of Bacillus subtilis. Surfactin showed excellent surface-active properties and prominent biological properties that may be important in various scientific and industrial fields. In this experiment. local isolate of B. subtilis denoted a B .subtilis 3M was used and cultured into the Cooper’s media. By using shake flask fermentation technique, various parameters of media compositions and fermentation conditions (in Cooper’s media) that affected surfactin and biomass production were optimized using response surface methodology (RSM). Glucose (20-60 g/L). ammonium nitrate (0.03-0.07 M). ferrous sulfate (40-200 uM) and manganese sulfate (0.5-2.5 mM) represented factors for media compositions. On the other hand, fermentation time (48-144 h). inoculum volume (1-20 %) and temperature (20-50 °C) were selected as factors for fermentation conditions. The ranges for each factor ,,were determined by applying one-factor-at-a-time (OFAT) optimization. Henceforth. central composite design (CCD) was employed combining with RSM to optimize both media compositions and fermentation conditions for the production of surfactin and biomass in the media culture. Thusly. the experimental data was fitted to a second-order polynomial equation using multiple regression analysis and analyzed using analysis of variance (/\NOV/\). The 3D response surface plots from the mathematical models were utilized to determine optimum conditions. For media compositions . optimal surfactin production ,was observed of Cooper's media supplemented with 43.-+ g/L glucose. 0.052 M ammonium nitrate. 140 p ii ferrous sulfate and 1.73 mM manganese sulfate. Under these conditions, the maximum predicted yield or surfaetin was 190.8 mg/L. As for fermentation conditions, optimal surfaetin production was observed of Cooper’s media in the conditions of 93 hours of fermentation time. 8.2 % or inoculum volume and 25 °C or temperature. Surfactin yield under these conditions was observed at 249. 7 mg/L. Thus. optimization or both media compositions and fermentation conditions by using RSM managed to enhance surfactin yield to some extent significantly than conventional Cooper's media.